2017
DOI: 10.1016/j.jmoldx.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Preanalytic Procedure for Performing the cobas HPV Test in SurePath Preservative Fluid

Abstract: The formation of chemical cross-links between nucleic acids and proteins in formalin-containing media presents challenges for human papillomavirus (HPV) testing of cervical samples collected in SurePath Preservative Fluid. A preanalytic process involving addition of a nucleophilic buffer and heating the sample to 120°C was developed to reverse the effects of cross-linking and improve nucleic acid accessibility for the cobas HPV Test in SurePath. Cycle threshold (C) values for cobas HPV detection were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this study, all liquid-based cytology samples were prepared using the preservation solution, "CytoRich Clear Preservative Fluid", which contains a mixture mainly composed of ethanol with small amounts of methanol and isopropanol, and has been confirmed to achieve superior DNA preservation for genomic analysis, compared with the conventional 95% ethanol-based fixation used in previous studies (27,28). After scraping off of all cytological material within an encircled spot, our single-shot MS analysis achieved identification of a total of 4,839 proteins in a relatively short time without fractionation, which is a comparable depth of proteome coverage to that reported in a previous study (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all liquid-based cytology samples were prepared using the preservation solution, "CytoRich Clear Preservative Fluid", which contains a mixture mainly composed of ethanol with small amounts of methanol and isopropanol, and has been confirmed to achieve superior DNA preservation for genomic analysis, compared with the conventional 95% ethanol-based fixation used in previous studies (27,28). After scraping off of all cytological material within an encircled spot, our single-shot MS analysis achieved identification of a total of 4,839 proteins in a relatively short time without fractionation, which is a comparable depth of proteome coverage to that reported in a previous study (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, correct preanalytical treatment of samples counters the impact of formaldehyde [44]. Furthermore, studies with BD Onclarity [16,17], Hologic Aptima [45,46], Roche cobas [47,48] and Genomica CLART HPV2 [49] have previously shown that Sure-Path collected samples can safely be used for HPV analysis. ThinPrep collected LBC medium on the other hand does not contain formaldehyde and consequently is considered less challenging with respect to HPV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies with BD Onclarity (16,17), Hologic Aptima (45,46), Roche cobas (47,48) and Genomica CLART HPV2 (49) have previously shown that SurePath collected samples can safely be used for HPV analysis. ThinPrep collected LBC medium on the other hand does not contain formaldehyde and consequently is considered less challenging with respect to HPV testing.…”
Section: Discussionmentioning
confidence: 99%